Enhanced Performance of Proliferation Assay of Bone Marrow Cells by Optimizing in vivo Incorporation of 5-Ethynyl-2′-Deoxyuridine and Cell Preparation for Flow Cytometry. (1st September 2016) - Cui, Xianghua; Fan, Xu; Zhang, Dong; Jia, Jidong
ABSTRACT: The characterization of DNA synthesis and cell proliferation in vitro by 5-ethynyl-2′-deoxyuridine (EdU) incorporation is widely used, but this has not been optimized for in vivo use. In this study, the administration route, dose (0–50 mg kg −1 ), and incorporation duration (0–72 h) of EdU and the procedure of cell preparation for flow cytometry were optimized for in vivo proliferation assay in bone marrow cells. The percentage of EdU-positive bone marrow cells was higher following intravenous than intraperitoneal injection ( p  < 0.05); the percentage of positive cells increased in a dose-dependent manner from 0 to 50 mg kg −1 ( p  < 0.05); and the optimal dose was 25 mg kg −1 . However, the percentage of positive cells was not affected by the duration of incubation in vivo from 12 to 72 h ( p  > 0.05). False-positive signals observed during flow cytometry were markedly reduced by subtracting the signals generated by nonviable cells stained with 7-amino-actinomycin. In addition, the percentage and mean fluorescence intensity of EdU-positive cells were increased by adding a signal enhancer to block background staining. In conclusion, the optimized procedures for in vivo incorporation of EdU and cell preparation for flow cytometry markedly improved the specificity and sensitivity of the proliferation assay of bone marrow cells.